Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1158/1055-9965.epi-21-0753
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Ischemic Stroke in Head and Neck Cancer Patients and Those Who Were Treated with Radiotherapy: A Population-Based Cohort Study

Abstract: Background: To investigate the standardized incidence ratios (SIR) of stroke in patients with head and neck cancer and their relationship to radiotherapy. Methods: Patients with head and neck cancer ages 20–85 years were enrolled from 2007 to 2016 using the Taiwan Cancer Registry. The study endpoint was fatal and non-fatal ischemic stroke, ascertained by the National Health Insurance Research Database. Age- and sex-adjusted S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
0
14
2
Order By: Relevance
“…Furthermore, nasopharyngeal carcinoma was excluded from their main analysis. We also note that the cohorts in the studies by Yeh et al and Kim et al predominately represented oral subsites (approximately 95% and 72%, respectively). In comparison, our cohort comprised of 48% nasopharyngeal, 18% oral cavity, and 13% laryngeal tumors.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Furthermore, nasopharyngeal carcinoma was excluded from their main analysis. We also note that the cohorts in the studies by Yeh et al and Kim et al predominately represented oral subsites (approximately 95% and 72%, respectively). In comparison, our cohort comprised of 48% nasopharyngeal, 18% oral cavity, and 13% laryngeal tumors.…”
Section: Discussionmentioning
confidence: 51%
“…A study by Kim et al reported an IRD of 5.88 strokes per 1000 PY with propensity-score matching. A study by Yeh et al used a method similar to ours and reported an SIRR of 1.37 for ischemic stroke. However, their study did not report on SIRD nor detail the stroke risks in different subpopulations within the HNC cohort.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…4,5 Ischemic stroke (IS) is a common post-RT complication that occurs at a rate of 17.32 per 1,000 person-years, with an incidence rate ranging from 10% to 34% among HNC survivors after RT. [6][7][8][9][10] Studies have reported that compared with the general population, patients with HNC had a standardized stroke incidence ratio of 1.37 7 and had a relative risk of IS ranging from 2.09 over a 5-year follow-up period to 10.1 over a 7-year follow-up period after RT. 8,9 .…”
Section: Introductionmentioning
confidence: 99%